Drivers and purposes of performance measurement : an exploratory study in English local public sector services - Micheli, Pietro (Cranfield University, 2007)
This dissertation focuses on the interactions between local public sector organisations and institutions in the development of performance measurement (PM) targets and indicators. The research is grounded in the performance measurement and management literature and adopts a joint new institutional and resource dependence perspective. Empirically, the research, which is qualitative and theory-building, consists of case studies undertaken in local public sector organisations in England. The iterative comparison of theory and data has enabled the investigation of a number of relevant themes. In the last decade, the British Government has placed great emphasis on the consistency of objectives, targets and indicators from national to local levels with the aim of enhancing performance, transparency and accountability, and of driving behavior. However, this research shows that the influence of several organizations and the co- existence of various PM initiatives generate confusion and overlaps locally. Moreover, in the cases considered the unmanageable number of indicators and the lack of clarity regarding the drivers and purposes of PM have led to confused massages and counter- productive approaches to the measurement and management of performance. From a theoretical view-point, the favourable comments expressed by interviewees regarding the current PM regime contrast with critics of New Public Management. Furthermore, legitimacy-seeking and efficiency-enhancing rationals have emerged as intertwined and loosely coupled. This is in opposition to what is maintained by early new institutional theorists. In line with resource dependence theory, PM systems were found to be significant components of power systems in organisations. Through the examination of the roles of PM and the investigation of relevant concepts such as 'golden thread' and performance culture, this research aims to make an impact on policy-making and to improve the ways in which targets and indicators are set and used, hence having a positive effect on the services delivered.
Keywords: Performance Measurement; Organisation Theory; Public Sector; Performance Management; Measurement Theory